2020
DOI: 10.1002/micr.30591
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of the impact of surgeon and hospital volume in microsurgical breast reconstruction

Abstract: Background Prior investigations of microsurgical breast reconstruction have not distinguished the effects of surgeon versus hospital volume and failed to address the effect of patient clustering. Our data‐driven analysis aims to determine the impacts of surgeon and hospital volume on outcomes of microsurgical breast reconstruction. Methods Nationwide Inpatient Sample (NIS) data from 2008 to 2011 was analyzed for patients who underwent microsurgical breast reconstruction. Volume‐outcome relationships were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Although the relationship between high volume and improved outcomes is well documented in the existing literature, examination of this association among DIEP flap reconstructions remains limited. 12,13,25 In the present work, high procedural volume was associated with reduced rates of systemic complications, such as respiratory, infectious, and thrombotic events. However, we did not observe a significant association between center volume and procedural complications.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although the relationship between high volume and improved outcomes is well documented in the existing literature, examination of this association among DIEP flap reconstructions remains limited. 12,13,25 In the present work, high procedural volume was associated with reduced rates of systemic complications, such as respiratory, infectious, and thrombotic events. However, we did not observe a significant association between center volume and procedural complications.…”
Section: Discussionmentioning
confidence: 53%
“…In congruence with our findings, Reid et al found increasing volume of all microsurgical breast reconstruction cases to be linked to lower costs. 25 The cost-effectiveness of complex operations at high-volume centers is likely due to more efficient intraoperative and postoperative care pathways established in experienced centers. Our findings may be particularly relevant in referral decisions and pay for performance paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…Given the propensity of higher volume hospitals to receive referrals of more complicated cases, our finding that high-volume hospitals were significantly less likely to have surgical complications is additionally noteworthy ( P =0.014). This holds true across the literature for other surgical procedures, including various general surgical procedures, cardiac surgical procedures, overall microsurgical procedures, free flap breast reconstructive surgery, craniosynostosis surgery, and orthognathic surgery 1,24–26,28 . High-volume hospitals experiencing fewer surgical complications could be because of surgeon experience, established multidisciplinary teams, and optimized care pathways for these procedures.…”
Section: Discussionmentioning
confidence: 98%
“…When examining patient costs and hospital volume, this study found that patient admission charges related to orthognathic operations at high-volume hospitals were significantly less than other hospitals ( P <0.001). This trend has been seen in various general surgery and plastic surgery procedures 23–26 . However, when analyzing other craniofacial procedures, a national study on cleft palate repair was unable to demonstrate associations between hospital volume and costs 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation